Correlation of serum tumor necrosis factor-α, interleukin-4 and soluble interleukin-2 receptor levels with radiologic and clinical manifestations in active pulmonary tuberculosis - Levent Kart; Hakan Buyukoglan; Ishak O. Tekin; Remzi Altin; Zuhal Senturk; Inci Gulmez; Ramazan Demir; Mustafa Ozesmi (Hindawi Limited, 2003)
The precise clinical manifestations of tuberculosis are likely to result from a complex interaction between the host and the pathogen. We took serum samples from a group of patients with a variety of clinical and radiological stages of pulmonary tuberculosis in order to characterize tumor necrosis factor-α (TNF-α), interleukin-4 (IL-4) and soluble interleukin-2 receptor (sIL-2R) response. We further evaluated whether the levels of TNF-α, IL-4 and soluble IL-2R are related with each other, and also evaluated the levels of TNF-α, IL-4 and sIL-2R after anti-tuberculosis therapy and relation with radiologic scores. Forty-three inpatients with active pulmonary tuberculosis and 19 healthy controls participated in the study. Patients were divided into four categories radiologically on chest X-ray (minimal, moderate-advanced, far-advanced and with miliary infiltration). Concentrations of TNF-α (20.9±10/15.4±8 pg/ml) and sIL-2R (2569±842/1444±514 pg/ml) were statistically different between patients and controls (p=0.02 and p=0.0001, respectively). Before chemotherapy there was a positive correlation between TNF-α and sIL-2R (r=0.34), but there was no correlation between IL-4 and TNF-α, and between IL-4 and sIL-2R (r=−0.23 and r=−0.22). The TNF-α level was not statistically different in four groups before and after chemotherapy. Results of this study provided some evidence confirming the previously reported role of TNF-α, IL-4 and sIL 2R in the control of tuberculosis, but these cytokines were not found related with disease severity.